WEARABLE NON-INVASIVE OPTICAL MONITORING FOR BLADDERDYSFUNCTION–IN CONTINENCE AND ENURESIS - Ms.Nivedha DR; M Sushmitha; Jayakumar; Lakshman G; Jamal Al Jazeer F (The Bioscan, 2024)
This study proposes a novel real-time monitoring system designed to continuously assess urinary bladder volume and promptly alert healthcare providers when the bladder is filled beyond normal limits. The system utilizes noninvasive ultrasonic sensors and advanced signal processing algorithms to measure bladder volume accurately. The collected data is transmitted wirelessly to a centralized platform accessible to medical professionals. Key features of the monitoring system include real-time data visualization, trend analysis, and intelligent alerting mechanisms. By employing machine learning algorithms, the system can adapt to individual patient patterns and provide personalized alerts, reducing false alarms and enhancing the overall accuracy of bladder volume assessments. The alerts are designed to intimate healthcare providers, facilitating timely intervention and preventive measures. The implementation of this monitoring system aims to improve patient care by addressing issues related to urinary bladder dysfunction, such as overfilling or inadequate emptying, which can lead to various medical complications. The proposed system has the potential to enhance patient outcomes, streamline healthcare processes, and contribute to the overall improvement of urological care.